Hot-stage microscopy for determination of API particles in a formulated tablet - Simek, Michal; Grünwaldová, Veronika; Kratochvíl, Bohumil (BioMed research international, 2014)
Although methods exist to readily determine the particle size distribution (PSD) of an active pharmaceutical ingredient (API) before its formulation into a final product, the primary challenge is to develop a method to determine the PSD of APIs in a finished tablet. To address the limitations of existing PSD methods, we used hot-stage microscopy to observe tablet disintegration during temperature change and, thus, reveal the API particles in a tablet. Both mechanical and liquid disintegration were evaluated after we had identified optimum milling time for mechanical disintegration and optimum volume of water for liquid disintegration. In each case, hot-stage micrographs, taken before and after the API melting point, were compared with image analysis software to obtain the PSDs. Then, the PSDs of the APIs from the disintegrated tablets were compared with the PSDs of raw APIs. Good agreement was obtained, thereby confirming the robustness of our methodology. The availability of such a method equips pharmaceutical scientists with an in vitro assessment method that will more reliably determine the PSD of active substances in finished tablets.
Keywords: farmaceutická chemie; Temperature; lidé; velikost částic; Chemistry, Pharmaceutical; mikroskopie; Tablets; teplota; Microscopy; tablety; Particle Size; Humans